Klášter premonstrátek v Doksanech v období středověku - Junová, Tereza (Charles University, 2020)
Keywords: doksany

Knihovny ženských klášterů v pohusitském období - Modráková, Renáta (Acta Musei Nationalis Pragae – Historia litterarum, 2020)
The libraries of Bohemian female monasteries were distinctive units with thematically diverse codices in both manuscript and printed form. This article focuses on their composition and possible transformation in the Post-Hussite period with an overlap to the 16th century. Five important nunneries of various orders have been chosen as models. These include St George’s Benedictine Convent at Prague Castle, the Premonstratensian Convent in Doksany, St Anne’s Dominican Convent in the Old Town of Prague, the Premonstratensian Convent in Chotěšov, the Convent of Poor Clares in Český Krumlov and the Convent of Poor Clares in Cheb. The composition and size of a particular library in the period under review depended on the economic, social and cultural situation of each convent. Liturgical books continued to be commissioned, but the number of devotional literature and mystical texts increased. Many monasteries also focused on ordering printed books. The primary aim of the article is to open the whole topic.
Keywords: chotěšov; doksany